Longitudinal assessment of stability of sensory features in children with autism spectrum disorder or other developmental disabilities. Issue 1 (8th September 2018) - Baranek, Grace T.; Carlson, Mike; Sideris, John; Kirby, Anne V.; Watson, Linda R.; Williams, Kathryn L.; Bulluck, John
Abstract : Prior research on the stability of sensory processing problems in children with autism spectrum disorder (ASD) or other developmental disabilities (DD) has produced inconsistent results. We employed a longitudinal study design to assess the stability of three clinical sensory response patterns: hyporesponsiveness; hyperresponsiveness; and sensory interests, repetitions, and seeking behaviors (SIRS). Parents of children with ASD ( n = 55) or DD ( n = 35) responded to sensory questionnaires at two time points (T1 and T2) separated by 3.3 years on average, with the children aged 2–12 years ( M = 5.69 ± 2.46) at the first assessment. For each sensory response pattern, regression analysis revealed that, for both ASD and DD groups, scores at T1 were strong predictors of scores at T2. Over the longitudinal assessment interval, there was a significant mean decline in severity for SIRS in both groups and for hyporesponsiveness in the ASD group. Parental estimates of the amount of therapy services received were positively associated with the severity of sensory features at T2, an outcome that may result from increased intervention dosages being administered to children who fail to improve over time. The results are discussed in terms of person‐centered and environmental considerations, which, in combination, have the capacity to affect stability outcomes for sensory features. Autism Research 2019, 12: 100–111 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Children with autism spectrum disorder (ASD) and other developmental disabilities (DD) may process sensory information differently from those who do not have ASD. For example, some children may be over‐responsive or under‐responsive to sound or touch. In this study, we showed that sensory features in preschool/school‐aged children with ASD and DD tend to decrease on average over a several year period. However, individual children tend to retain their ranking (low or high in sensory features) in comparison to other children over time.